Peripapillary Vessel Density Reversal after Trabeculectomy in Glaucoma. (26th June 2018) - In, Jung Hee; Lee, So Yeon; Cho, Seok Ho; Hong, Young Jae
Abstract : Purpose . To evaluate the microvascular changes at the peripapillary area and optic disc in glaucomatous eyes after IOP lowering by trabeculectomy using OCT angiography. Methods . 25 patients with primary open-angle glaucoma (POAG) who underwent trabeculectomy by a single surgeon were evaluated. Using optical coherence tomography angiography, vessel density was evaluated within the whole image, peripapillary, nasal region, and temporal region. Peripapillary vessel density was measured preoperative, 1 week, 1 month, and 3 months postoperatively in POAG patients. Reversal of vessel density was calculated for all analyzed areas. Results . The intraocular pressure (IOP) decreased from 30.92 ± 6.32 mmHg (range, 18–44) to 12.64 ± 3.35 mmHg (range, 8–22) at 3-month postoperatively. Compared with the preoperative baseline value, whole vessel density, peripapillary vessel density (PvD), and PvD in nasal region and temporal region were significantly increased at 3-month postoperatively. The magnitude of the vessel density reversal was significantly associated with higher preoperative IOP and greater IOP reduction. Conclusions . A significant increase in the peripapillary vessel density was demonstrated after trabeculectomy using OCT angiography. The reversal of peripapillary vessel density was associated with higher preoperative IOP and greater IOP reduction. Our postoperative results suggest that the ocular perfusion impairment by high intraocular pressure can be improved by IOP reduction, and the reversal of microvasculature may contribute to the rate of glaucoma progression.